Invented fairy tales in groups with onco‐haematological children. Issue 3 (14th May 2013) - Margherita, G.; Martino, M. L.; Recano, F.; Camera, F.
Abstract Background The impact of an onco‐haematological illness for children is a traumatic event that opens to pain, hospitalizations and interrupts the continuity of daily life. It is difficult for the child to make meaning, to share the pain or ask a question related to the illness because, often, the parents or doctors cannot find a way to communicate in a suitable way for the child who remains in a situation of 'unspoken', where, fear, anxiety and pain cannot find a space to express. Methods The present research‐intervention uses the methodology of invented fairy tales in groups with onco‐haematological children, in the hospital, in order to explore the organization of the meanings at the base of the tales co‐constructed by the participants underlying weaknesses and strengths of the invented fairy tales in groups intervention. The invented fairy tales in groups is used as a tool, such as a play, to express, share and support the experience of the illness of children. Forty‐nine children participated to the invented fairy tales in groups in an onco‐haematological hospital. Within a quali‐quantitative framework we performed a thematic analysis of elementary context, cluster analysis, on the fairy tales considered as a unique narrative corpus of the thought of the group. Results The analysis shows four thematic clusters: fantasy as search for a meaning, 29.71%, the group as a space for illusions, 27.90%, the illness as a family problem, 25.72%, anchoring reality, 16.67%. The results highlighted three main carriers of sense: the representation of illness/the relational world/the representation of the institution. Conclusions The use of invented‐fairy‐tales groups allowed the onco‐haematological children to tell and share the experience of illness through a different way, which let them express symbolically their pain. The invented fairy tale in groups becomes a mediator of psychic processes which offer new solutions while improving interpersonal relationships/communication between the participants in group.